Support for wilderness preservation: An investigation of the roles of place attachment and environmental worldview. (September 2021) - Wynveen, Christopher J.; Woosnam, Kyle Maurice; Keith, Samuel J.; Barr, Joseph
Abstract: Wilderness areas worldwide continue to face a range of threats, however public support for wilderness areas is lacking. Similarly, there is a paucity of research literature pertaining to public support for federally-designated wilderness areas within the U.S. Borrowing from the broader pro-environmental behavior literature, the purpose of this investigation was to explore the role that individuals' environmental worldview and place attachment play in their support for wilderness. Specifically, we asked residents of the southeastern United States about their political and financial support for the management and continued protection of current wilderness areas. Data was obtained via an online panel of adults who had visited a protected natural area in the previous five years. Confirmatory factor analysis and path analysis results revealed that place attachment partially mediated the relationship between environmental worldview and support for wilderness preservation. The data suggest that models of pro-environmental behavior, generally, and wilderness preservation, specifically, should include both a measure of general environmental beliefs and a measure of an individual's thoughts and feelings ascribed to a specific setting. Highlights: Wilderness area support is associated with a visitor's environmental beliefs and the bond they develop with the area. Managers should continue to seek to understand the reasons for visitors' place attachment intensity levels. Managers should continue to engage visitors with programs that increase visitors' place attachment to their wilderness area.